Instagram @ariamphibia Social Media Content Management in Building Personal Branding (January - December 2023) - Muhammad Faruq Iqbal; Erwan Sudiwijaya (Jogjakarta Communication Conference (JCC), 2024)
Indonesia is a country with abundant natural wealth and scenery. The richness and abundance of scenery is an attraction for landscape photographers. One of the many landscape photographers is Ari Amphibia. Ari Amphibia has routinely built personal branding as a landscape photographer through Instagram social media. With proper Instagram social media content management, it will result in strong personal branding.  The results of Ari Amphiba's published work have made him a brand ambassador for Fujifilm X Photographer Indonesia, Lowerpro Bag and Haida Filter Photographer. This research aims to find out the content management of @ariamphibia's Instagram social media in building personal branding. This research uses descriptive qualitative by involving three stages, namely data presentation, data reduction, conclusion drawing. The data collection techniques used include interviews and documentation. Data validity uses source triangulation. This technique is a testing process that aims to test the credibility of data by checking data that has been obtained through several data sources. The findings used four stages of content management, namely (1) Share; (2) Optimize; (3) Manage; (4) Engange. Then the next stage is using personal branding, namely (1) Think; (2) Brand Assement; (3) Focus; (4) Publish. The results of this study Ari Amphibia has carried out content management in building his personal branding on Instagram. However, this is still not enough, there is some content uploaded via Instagram outside of landscape photography. As a result, the personal branding created is not optimal and does not utilize the bio link feature on Instagram properly.